Functional level of rat liver tryptophan 2,3-dixoygenase messenger RNA during superinduction of enzyme with actinomycin D. - Killewich, L (1975)
Tryptophan 2,3-dioxygenase [EC 1.13.11.11; L-tryptophan:oxygen 2,3-oxidoreductase (decyclizing)] activity is induced by glucocorticoid hormones and superinduced by actinomycin D. Previous experiments had shown that hormonal induction of the enzyme activity is accompanied by parallel increases in tryptophan 2,3-dioxygenase mRNA level. In this study, we measured the tryptophan 2,3-dioxygenase mRNA levels during superinduction as well as hormonal induction, to determine whether superinduction of the enzyme activity is also mediated through changes in mRNA concentration. Tryptophan 2,3-dioxygenase mRNA was measured in a Krebs ascites cell-free protein synthesizing system supplemented with rabbit reticulocyte initiation factors. We found that during superinduction of the enzyme activity by actinomycin D, the mRNA level is identical to that of the actinomycin D-free controls. Our results do not, therefore, support the hypothesis that hormonal induction and/or superinduction of tryptophan 2,3-dioxygenase mRNA are regulated by a rapidly turning over repressor.